Síndrome de Marfan, mutaciones nuevas del gen FBN1 - Muñoz, Juan Sebastian; Saldarriaga Gil, Wilmar; Isaza de Lourido, Carolina (Iatreia, 2014)
Marfan syndrome (SM) is a systemic disorder caused by mutations in the extracellular matrix protein fibrillin 1 (FBN1). With a dominant autosomal pattern, SM patients are characterized by ocular, cardiovascular and skeletal involvement, all within a variable clinical spectrum. It has been suggested that the intrafamilial and interfamilial phenotypic variability, characteristic of the syndrome, occurs by the association of other mutations called driver mutations. Even though there is a clear genetic causation, the recently described driver mutations are not yet fully elucidated. We present a SM case with a mutation not previously described in the fibrilin 1 gene, applying the revised Ghent nosology and analyzing the role of this new mutation and of the driver mutations in the genesis of the disease.